(untitled) (Desarrollo, Estado y Espacio, 2022)
This paper analyses the actions of the national, provincial and local states specifically related to territorial development and the promotion of non-conventional hydrocarbon production in the province of Neuquén in the period 2012/2020, focusing on two localities: Rincón de los Sauces and Añelo. The aim is to understand the particular way in which some of the trends of globalisation and the process of neoliberalisation have been forged in the area, while at the same time driving transformations in the territorial organisation of space and in the configuration of the state itself. Methodologically, a qualitative approach based on official secondary sources and primary data from fieldwork in the province and localities was used. The obtained results indicate that, throughout the period, there were advances and setbacks in the constitution of a new institutional arrangement that modified the barriers to the sustainable accumulation of capital by large hydrocarbon companies. It was also observed that the Vaca Muerta region, and particularly the localities under study, are observed, analysed, planned and projected by a multiplicity of actors that are reproduced at different scales, indicating the strategic relevance acquired by the region in the last decade.